Generation and preclinical immunogenicity study of dengue type 2 virus-like particles derived from stably transfected mosquito cells - Amporn Suphatrakul (2018)
© 2015 Elsevier Ltd. Recent phase IIb/III trials of a tetravalent live attenuated vaccine candidate revealed a need for improvement in the stimulation of protective immunity against diseases caused by dengue type 2 virus (DENV-2). Our attempts to develop particulate antigens for possibly supplementing live attenuated virus preparation involve generation and purification of recombinant DENV-2 virus-like particles (VLPs) derived from stably (prM+E)-expressing mosquito cells. Two VLP preparations generated with either negligible or enhanced prM cleavage exhibited different proportions of spherical particles and tubular particles of variable lengths. In BALB/c mice, VLPs were moderately immunogenic, requiring adjuvants for the induction of strong virus neutralizing antibody responses. VLPs with enhanced prM cleavage induced higher levels of neutralizing antibody than those without, but the stimulatory activity of both VLPs was similar in the presence of adjuvants. Comparison of EDIII-binding antibodies in mice following two adjuvanted doses of these VLPs revealed subtle differences in the stimulation of anti-EDIII binding antibodies. In cynomolgus macaques, VLPs with enhanced prM cleavage augmented strongly neutralizing antibody and EDIII-binding antibody responses in live attenuated virus-primed recipients, suggesting that these DENV-2 VLPs may be useful as the boosting antigen in prime-boost immunization. As the levels of neutralizing antibody induced in macaques with the prime-boost immunization were comparable to those infected with wild type virus, this virus-prime VLP-boost regimen may provide an immunization platform in which a need for robust neutralizing antibody response in the protection against DENV-2-associated illnesses could be tested.